2009
DOI: 10.1080/00365540902849391
|View full text |Cite
|
Sign up to set email alerts
|

Acute bacterial meningitis in adults: Predictors of outcome

Abstract: Case fatality ratio and permanent sequelae of acute bacterial meningitis remain high in recent decades. A prospective longitudinal study of adult patients admitted with community acquired acute bacterial meningitis at a tertiary infectious diseases unit aimed to identify predictors of unfavourable outcome - death and sequelae. Anamnestic, clinical and laboratory data and clinical outcome were recorded. From 1997 to 2006, 279 adults (122F, 157M) with a median age of 51 y were admitted with acute bacterial menin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 24 publications
2
44
5
2
Order By: Relevance
“…This has been a consistent finding in earlier studies too [2,9,[17][18][19]. It has been shown in a previous study that there is an independent incremental association between delays in administrating antibiotics and mortality from adult ABM [20].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This has been a consistent finding in earlier studies too [2,9,[17][18][19]. It has been shown in a previous study that there is an independent incremental association between delays in administrating antibiotics and mortality from adult ABM [20].…”
Section: Discussionsupporting
confidence: 77%
“…In our study, 26 patients (6.84%) had seizures which were less than reported in a recent study (17%) [17]. However, in the poor outcome group, the frequency of seizures was 17.6% (6/34 patients).…”
Section: Discussioncontrasting
confidence: 77%
“…Several studies have shown that early diagnosis and treatment can significantly improve the prognosis of bacterial meningitis 24,25. The clinicians involved in this study were fully aware that bacterial meningitis is an important potential postoperative complication and that once PNBM is diagnosed, antibiotic therapy should be administered as soon as possible; this would have effectively improved the prognosis of the patients in this study 26. This may also explain the low mortality rate observed (only one patient died, due to respiratory insufficiency).…”
Section: Discussionmentioning
confidence: 96%
“…1 Glucose is mainly transported into the CSF by facilitation across the choroid plexus and the ventricular and subarachnoid capillary system while some of it is transported by simple diffusion. Current theories postulate that the pathogenesis of hypoglycorrhachia is multifactorial and includes inhibition of glucose entry into the subarachnoid spaces due to alterations in the blood brain barrier 6 , increased rate of glucose transport across the arachnoid villi, increased glycolysis by leucocytes and bacteria 17 and increased rate of metabolism in the brain and spinal cord.…”
Section: Discussionmentioning
confidence: 99%